1998
DOI: 10.1074/jbc.273.2.1086
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA-binding Proteins and Neuron-restrictive Silencer Factor Participate in Cell-specific Transcriptional Control of the NMDAR1 Gene

Abstract: Our previous studies revealed that a proximal region of the N-methyl-D-aspartate receptor 1 (NMDAR1) promoter is important for cell-type-specific expression. We have now explored the contributions of several regulatory elements to this specificity. Deletion of the neuronrestrictive silencer element partially relieved the suppression of promoter activity in C6 glioma and HeLa cells. An overlapping G(C/G)G/tandem Sp1-containing region crucial for both basal and nerve growth factor (NGF)-regulated promoter activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…5B), and therefore factors binding to double-stranded DNA are unlikely to replace Sp1 from the NR1 promoter. Other potential candidates may be single-stranded DNA-binding proteins that can also be activated by NGF and bind to the same promoter region as revealed by our previous studies (51). In that report, we observed that single-stranded DNA-binding complex 2 interacted with a T(G) 3 A sequence overlapping the GC boxes, but in a single-stranded DNA conformation only, and NGF treatment of PC12 cells for 30 min increased this interaction significantly.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…5B), and therefore factors binding to double-stranded DNA are unlikely to replace Sp1 from the NR1 promoter. Other potential candidates may be single-stranded DNA-binding proteins that can also be activated by NGF and bind to the same promoter region as revealed by our previous studies (51). In that report, we observed that single-stranded DNA-binding complex 2 interacted with a T(G) 3 A sequence overlapping the GC boxes, but in a single-stranded DNA conformation only, and NGF treatment of PC12 cells for 30 min increased this interaction significantly.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, transcription factors interacting with this GSG/GC box region could be the nuclear target(s) of the Ras/ERK cascade. In our previous studies, we showed that Sp1, Egr-1, and single-stranded DNA-binding proteins may interact with this region (22,39,51). ERK regulation of gene transcription can be mediated by two pathways: phosphorylated ERKs enter into the nucleus and modify transcription factors directly (4, 5), or ERKs may modify cytoplasmic ribosomal S6 kinase that translocates to the nucleus and regulates transcription (6).…”
Section: Discussionmentioning
confidence: 99%
“…There is no DNA sequence with more than 65% homology to the initiator (Inr) consensus, YYANWYY, because the initiator may direct transcription initiation for most genes (45). We also did not find an RE1/NRSE site using the same searching criteria to the consensus, TTCAGMACCDYGSASAGHRCC (46), considering that the RE1/NRSE DNA cis-element plays an important role in neuronal expression (41).…”
Section: Resultsmentioning
confidence: 91%
“…A consensus of GC-Box (Sp1 site) from Promega was used as a competitor. Results of EMSA were analyzed and quantified with a PhosphorImager as described in our previous studies (41).…”
Section: Methodsmentioning
confidence: 99%
“…A 27-bp GCrich region (GC-box) proximal to the transcription start sites has been identified that controls induction of the Grin1 gene upon differentiation of P19 cells, and this site is recognized by Sp1 and myc-associated zinc finger protein transcription factors (Okamoto et al, 2002). These sites previously were known to respond to Sp1, -3, and -4 transcription factors Kusiak, 1995, 1997;Bai et al, 1998;Liu et al, 2001) and interact with an element further 5Ј in the promoter (Ϫ520/Ϫ529) that is recognized by myocyte enhancer factor 2C (Krainc et al, 1998). Studies with Grin1 promoter constructs in PC12 cells suggest that NGF uses both the Ras/extracellular signal-regulated kinase (ERK) and phosphatidylinositol 3-kinase pathways to up-regulate Grin1 promoter activity through Sp1 (Liu et al, 2001).…”
Section: B Kainate Receptors Grik1 To Grik5mentioning
confidence: 99%